The Effect of Translanguaging on Student’s Self Efficacy in Speaking English - 'Ulya, Muhimmatul; Masruroh, Lailatul (Lingual Journal of Language and Culture, 2024)
The aim of this study was to identify the effect of translanguaging on students’ self-efficacy in speaking. This research used procedure text of personal money management. Translanguaging is a process of creating meaning, shaping experience, acquiring understanding and knowledge by using two languages (Baker, 2011). Recently, it is a suitable strategy for teaching and learning language, especially to gain self-efficacy in speaking English because it gives students freedom to dynamically use their L1 and L2 repertoire which can create safe environment and reducing anxiety in speaking by implementing translanguaging concepts; stance, design, and shift (Carstens, 2016; Vogel & García, 2017; D. Wang, 2019). Then, the subjects were students at SMA Negeri 1 Dukun Mentaras, Dukun, Gresik. This research consists of around 72 eleventh graders students as samples and used quasi-experimental which had an experimental class and control class. Pre-intervention test, treatment, and post-intervention test are the tools used in this research to gather data. Based on the data analysis by comparing the result of pre and post test data of experimental group in Wilcoxon signed-rank (p-value 0.135) and the post test data of control and experimental group in Mann-Whitney U (p-value 0.386), there is no significant improvement on self-efficacy in students speaking English of the experimental group after treatment. It is due to the complication in implementation of translanguaging concepts that are explained in discussion.